INFORMATION SECURITY MANAGEMENT STRATEGY ANALYSIS USING SYSTEM DYNAMICS MODELING - Arie Marbandi; Ahmadi Ahmadi; Adi Bandono; Okol S Suharyo (JOURNAL ASRO, 2018)
Handling information security management is an absolute thing to do for organizations that have information systems to support the organization's operations. Information systems consisting of assets both software and hardware that manage data and information that are spread over networks and the internet, make it vulnerable to threats. Therefore investment and costs are needed to secure it. Costs incurred for this need are not small, but investment expenditures and information security costs carried out need serious handling to be more effective and on target. The System Dynamics Model is used to evaluate alternative strategies to demonstrate the effectiveness of investment and the cost of managing information security through simulation of policy changes. System Dynamics are methods for describing models and systems analysis that are dynamic and complex, consisting of variables that influence each other in the form of causal relationships and feedback between variables that are either reinforcing or giving balance. Simulation using a dynamic system model in this study illustrates that the management of risk assessment followed by vulnerability reduction efforts has a very large impact on the management of information security. By making a difference in the value of security tools investment, this provides an alternative choice in information security risk management investments to achieve the effectiveness of the overall costs incurred in managing information security